Towards a new European Coastal Mineral Aggregates Planning Regime - Bert Van der Moolen; Ian Wilson (European Journal of Spatial Development, 2003)
A project plan was recently presented in the Netherlands with a view to extracting the riverbed area of the Heesseltsche Uiterwaarden. This is part of the much larger Fort St. Andries project. The area of the Heeseltsche Uiterwaarden is 350 hectares and lies between the villages of Tiel and Neerijnen. In the Environmental Impact Assessment it was concluded that the present ecological values will be affected by the extraction of clay and the dumping of slightly polluted slib. Besides these effects, there is the possibility of negative external effects on traffic and noise. The local inhabitants are organising themselves in a local action committee and are opposing Rijkswaterstaat, which is the formal decision maker for this project. They think that the project includes much that is not necessary. The only thing that they in fact want to see is an increase in protection against extreme high water tides, due to heavy rainfall such as occurred in 1995. At that time most of the area had in fact to be evacuated. There are many of these examples in the Netherlands where local interests conflict with projects of regional, national or even international interest. As such, simple top down organisation of, and an easy commitment to, large -scale spatial developments seems to be no longer acceptable to a majority of the people. A new way of planning and organising is thus needed in order to help realise such projects, most of which inevitably have an enormous impact at the local level. Projects in this category include the Betuwe- and HSL-rail line, the F3B mineral extraction aggregates site, the fifth runway for Schiphol airport, etc (see for example Voogd and van der Moolen, 1995). These examples have to be considered not only in themselves, but also in their larger political context. The social context in terms of authority and legitimacy is changing, particularly with regard to the way in which people react to one another. In the Netherlands the year 2002 must be seen as being of particular importance in this regard, especially as it heralded the dramatic arrival of several new political parties, i.e. ‘Leefbaar Nederland‘ and ‘Lijst Pim Fortuijn’. Instead of the so-called ‘regenteske’ way of dealing with political matters, there should be more transparency, openness and a greater measure of clarity in the way things are decided and organised. Without the pretension to give an accurate description, we could however describe this process as a ‘peoples movement to achieve more power’. We believe this is also reflected in the planning processes of modern large-scale projects in our countries. With respect to mineral aggregates extraction, we have clearly underestimated the management tasks attached to mineral resources according to Neeb and Dahl (2002). It remains a mystery as to why there is so little attention paid to, or appreciation of, mineral aggregates planning. For a long time little attention was paid to what we now call sustainable development. According to MMSD (2002) ‘in the context of the minerals sector, the goal of sustainable development should be to maximise the contribution to the well being of the current generation in a way that ensures an equitable distribution of its costs and benefits, without reducing the potential for future generations to meet their own needs’. Land use management should recognise competing interests and attempt to negotiate according to an integrated land use planning. We feel that the mineral aggregates are not fully appreciated. European Journal of Spatial Development-http://www.nordregio.se/EJSD/-ISSN 1650-9544- Articles Nov 2003- no 1 3 In this paper we attempt to describe this process from the viewpoint of mineral aggregates extraction, with examples from Great Britain and the Netherlands. We will conclude with a proposal on how to deal with such matters in a different way in future.